Probing a Dark Decade: Recordkeeping in the Indian Affairs Branch, 1937–1947 - Russell, Bill (Archivaria)

(untitled) (Association of Canadian Archivists, 2023)
At the end of the Second World War, the Indian Affairs Branch (IAB) launched a significant administrative renovation. As a result, during the first post-war decade, it introduced a number of notable changes in the manner in which records were managed both at headquarters in Ottawa and in the wide network of field offices. These achievements are documented in the archival record available today at Library and Archives Canada (LAC). What is less well understood is the records management environment out of which these changes emerged. This study describes aspects of the challenges that faced the IAB’s records staff during the later years of the Great Depression and those of the Second World War. Its centrepiece is a file that provides a chronicle, in the form of monthly reports, of recordkeeping in the headquarters central registry office of the Indian Affairs Branch during the years 1937–1947. This record shines additional light on the information management activities of the branch during a particularly difficult decade in the administration’s history.